2021
DOI: 10.1002/admt.202000963
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Multilayer Photonic Metamaterials: Fundamentals and Applications

Abstract: Graphene is given high expectation due to their unique properties and advantages and has revolutionized different research fields and leads to enormous applications. However, monolayer graphene shows limited absorption due to the ultrathin thickness, which compromises the optical modulation capability. Therefore, graphene metamaterials consisting of alternatively stacked graphene and dielectric layers or graphene layer combined with conventional metamaterial structures are proposed as artificially structured m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 138 publications
(357 reference statements)
0
24
0
Order By: Relevance
“…[66][67][68][69][70][71] More information about the linear and nonlinear optical responses of the graphene metasurfaces can be found in a recently published review. [72] HHG processes have been extensively studied for their application of generating coherent attosecond radiations in the extreme ultraviolet and soft X-ray regimes. [16] HHG methods are widely used to generate attosecond or even zepto-second pulses, which are instrumental in studying electron motion in materials.…”
Section: Graphene and Black Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation
“…[66][67][68][69][70][71] More information about the linear and nonlinear optical responses of the graphene metasurfaces can be found in a recently published review. [72] HHG processes have been extensively studied for their application of generating coherent attosecond radiations in the extreme ultraviolet and soft X-ray regimes. [16] HHG methods are widely used to generate attosecond or even zepto-second pulses, which are instrumental in studying electron motion in materials.…”
Section: Graphene and Black Phosphorusmentioning
confidence: 99%
“…[ 66–71 ] More information about the linear and nonlinear optical responses of the graphene metasurfaces can be found in a recently published review. [ 72 ]…”
Section: Harmonic Generation In Ldmsmentioning
confidence: 99%
“…Kim et al further reported thick h-BN flakes with 100 layers showing strong SHG similar to few-layer h-BN, confirming that thick h-BN flakes can serve as a nonlinear optical platform with its advantage of easy exfoliation 23 . Popkova et al first reported third-order nonlinearity of h-BN flakes with thicknesses ranging from 5 to 170 nm, determining that the h-BN third-order susceptibility χ (3) =8.4×10 -21 m 2 /V 2 , which is comparable to the cubic susceptibility of Si 3 N 4 24 . For all-optical communication systems, high optical nonlinearity is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, using a unique solution-based largescale synthesize method, we developed free-standing h-BN films with high mechanical strength 25 . The third-order optical nonlinearity of such free-standing h-BN thin films was revealed and their complex nonlinear susceptibility χ (3) was characterized by using the Z-scan technique. We report, for the first time, laser modified optical nonlinearity in a free-standing h-BN film, which significantly enhances the nonlinear refraction index n 2 by more than 20 times.…”
Section: Introductionmentioning
confidence: 99%
“…The polarization of electromagnetic (EM) wave is crucial in electromagnetic wave propagation, which has aroused increasing attention and interest, especially in the visible spectrum [1][2][3] . How to regulate the polarization form of EM wave in the process of propagation optionally is an essential and persistent research hotspot, which has fascinating application prospects from microwave to visible light [4][5][6][7][8] , such as spectroscopic analysis 9,10 , sensing 11,12 , and polarization imaging 13 . Conventional approaches to manipulate the polarization state of light using birefringent crystals and grating structures are subject to bulky waveplates [14][15][16] , thus the inherent defects of the conventional polarizers are large geometry and low efficiency in natural materials, which are difficult to meet in the current miniaturization of microwave and optical system integration.…”
Section: Introductionmentioning
confidence: 99%